The identification of articular cartilage and growth plate extracellular matrix-specific proteins supportive of either osteogenesis or stable chondrogenesis of stem cells - Kelly, Daniel (My University, 2020)
Tissue-specific extracellular matrix (ECM) proteins can play a key role in regulating the fate of stem cells and can potentially be utilized for therapeutic applications. Realising this potential requires further characterization of the diversity of biomolecules present in tissue-specific ECMs and an evaluation of their role as regulatory cues for regenerative medicine applications. The goal of this study was to identify specific soluble factors within the ECM of articular cartilage (AC) and growth plate (GP) that may impart chondro-inductivity or osteo-inductivity respectively. To this end, the significantly different proteins between both matrisomes were searched against the STRING database platform, from which C-type lectin domain family-11 member-A (CLEC11A) and S100 calcium-binding protein-A10 (S100A10) were identified as potential candidates for supporting osteogenesis, and Gremlin-1 (GREM1) and TGF-β induced gene human clone-3 (βIGH3) were identified as potential candidates for supporting stable chondrogenesis. Stimulation of chondrogenically-primed bone marrow-derived stem cells (BMSCs) with the AC-specific proteins GREM1 and βIGH3 had no noticeable effect on the deposition of collagen-II, a marker of chondrogenesis, but appeared to suppress the production of the hypertrophic marker collagen-X, particularly for higher concentrations of GREM1. Stimulation with GREM1 was also found to suppress the direct osteoblastic differentiation of BMSCs. In contrast, stimulation with the GP-specific factors CLEC11A and S100A10 was found to enhance osteogenesis of BMSCs, increasing the levels of mineralization, particularly for higher concentration of CLEC11A. Together these results demonstrate that AC- and GP-specific proteins may play a key role in developing novel strategies for engineering phenotypically stable articular cartilage or enhancing the regeneration of critically-sized bone defects.
Keywords: Cartilage; Extracellular matrix; Growth plate; Matrisome